The Empowerment of Green Technology Knowledge Among Stakeholder in Construction Industry - Yee Ching, Lim; Sarpin, Norliana; Masrom, Md Asrul Nasid; Kai Chen, Goh; Khalid, Zailawati (Research in Management of Technology and Business, 2022)
Green technology in Malaysia construction industry has seen substantial growth in the current years. However, a lack of knowledge about green technology among stakeholder in the construction industry in Malaysia remains an obstacle. Stakeholders does not properly understand the concept of green technology despite their concern about environmental negative effect. Therefore, the objectives of this research is to determine the current understanding of green technology knowledge among the stakeholder in the construction industry, to study the challenges of green technology knowledge acquirement faced by stakeholder in the construction industry and to suggest strategies to empower the green technology knowledge in construction industry. The scope of this research is to determine the current understanding of knowledge related to green technology among the stakeholder in the construction industry in Sabah, Malaysia. The research method of this study is quantitative method where a questionnaire survey was distributed to respondent from well experienced contractors that involved in construction project that use green technology. The data was collected from 76 respondents which represent 88% response rate among contractor in Sabah. The data were then analysed using Statistical Package for Social Science (SPSS) software for analysed on descriptive statistic to obtain the result. The result shows that the understanding of green technology concept is protection of the environment. While the biggest challenges of acquirement in green technology knowledge is lack of guideline from the available source. In addition, the research suggested the strategies to empower the green technology knowledge in construction industry is government policy. In conclusion, this research can potentially help policy makers, industry stakeholders, and advocates to understanding related to the empowerment of green technology knowledge and consequently in improving the application of green technology in construction project.